Pengaruh Penggunaan Aplikasi Keuangan Digital Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Aisyah, Widya Nur; Mardani, Ronny Malavia; Ramadhan, Tri Sugiarti (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study aims to analyze the effect of using digital financial applications, consisting of mobile banking and internet banking, on the financial performance of banking companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Financial performance is measured using financial ratios, namely Return On Assets (ROA), Return On Equity (ROE), and Net Interest Margin (NIM). The research method employs a quantitative approach using secondary data from the annual financial reports of banking companies. The sampling technique used is purposive sampling, with a sample size of 14 companies meeting the research criteria. Data analysis is conducted using simple regression analysis to determine the magnitude of the independent variables' influence on the dependent variable, assisted by SPSS version 25. The results indicate that the use of digital financial applications does not significantly affect ROA and ROE. However, it significantly affects the NIM ratio. This finding suggests that the utilization of digital banking services has a greater impact on net interest income than on overall profitability. Keywords: Mobile Banking, Internet Banking, Financial Performance, ROA, NIM